Survival of an epidemic MDR strain of Mycobacterium tuberculosis and its non-prosperous variant within activated macrophages - Yokobori, Noemi (2019)
Fil: Yokobori, Noemi. Instituto de Medicina Experimental (IMEX)-CONICET-Academia Nacional de Medicina, Pacheco de Melo 3081, C1425AUM Buenos Aires, Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET), Buenos Aires; Argentina.